OPTIMIZATION OF FLOOR CERAMIC PRODUCTION PROFIT USING SIMPLEX METHOD AND SENSITIVITY ANALYSIS - Sukmono, Thedjo; Alfan, Demas Bani (Antis-Publisher, 2025)
Objective: This study aims to find the optimal production strategy by considering these limitations. Method: Simplex method based on linear programming using LINGO software is applied to determine the best production combination. Results: The results of the analysis show that to obtain optimal profits of Rp680,963,542, the company needs to produce 14,815 m² of 60×60 granite, 21,297 m² of 60×60 ceramic, and 8,334 m² of 60×120 ceramic. This figure is 3% higher or equivalent to IDR 21,103,292 compared to the initial profit of IDR 659,860,250. Sensitivity analysis shows that all selected production variables have a reduced cost of zero, indicating that production conditions are optimal. A price change to the lower bound could potentially decrease revenue by 5% to Rp625,515,731, while an increase in price to the upper bound could increase revenue by 13% to Rp745,599,549. This result shows that there is flexibility in adjusting prices to maximize profits. Novelty: The problem of optimization in achieving maximum profit due to limited machine capacity and production targets is a challenge for ceramic companies.